Evaluasi Dampak Pembangunan Kawasan Ekonomi Khusus terhadap Pertumbuhan Ekonomi di Provinsi Kepulauan Riau - Muhammad Mufti Hudani; Nindya Eka Sobita; Vitriyani Tri Purwaningsih; Thomas Andrian (Lembaga Pengembangan Kinerja Dosen, 2025)
Special Economic Zones (SEZs) are designated areas within Indonesia established to perform specific economic functions and granted special incentives. The Indonesian government promotes equitable growth through various strategies, including SEZ development. The Riau Islands Province (Kepri) hosts the highest number of SEZs in the country. This decision reflects strategic considerations, as the province offers strong potential for SEZ expansion. Its geographic advantage along major international shipping routes and near Singapore and Malaysia makes Kepri a key hub for national and regional economic growth. Additionally, the province benefits from relatively developed infrastructure and strong local government commitment to SEZ support. This study evaluates the impact of SEZs on economic growth in the Riau Islands Province using a Difference-in-Differences (DiD) linear regression approach at the district/city level. The results show that, after SEZs became operational, districts/cities with SEZs recorded an average economic growth rate 0.135 percentage points higher than those without SEZs.